1982
DOI: 10.1002/1097-0142(19820515)49:10<2161::aid-cncr2820491029>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Thorotrast-induced hepatic angiosarcoma, and combined hepatocellular and cholangiocarcinoma in a single patient

Abstract: A 64-year-old man developed hepatic angiosarcoma, and combined hepatocellular and cholangiocarcinoma, 36 years after Thorotrast administration. The patient presented with a large mass in the right upper quadrant. His serum a-fetoprotein increased from 800 ng/ml to 51.2 &ml, and liver biopsy disclosed hepatocellular carcinoma. At autopsy, the liver had two different malignant neoplasms; angiosarcoma and combined hepatocellular and cholangiocarcinoma. Metastases of angiosarcoma to both lungs and of cholangiocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Second, a small portion of undifferentiated spindle cells expressed pan‐cytokeratin, suggesting that the sarcomatoid lesion was derived from HCC. Simultaneous occurrence of angiosarcoma and cHCC‐CCA has been previously reported in a single patient treated with Thorotrast . In that case, carcinoma lesions and angiosarcoma lesions were distributed separately, with overlap in several areas.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Second, a small portion of undifferentiated spindle cells expressed pan‐cytokeratin, suggesting that the sarcomatoid lesion was derived from HCC. Simultaneous occurrence of angiosarcoma and cHCC‐CCA has been previously reported in a single patient treated with Thorotrast . In that case, carcinoma lesions and angiosarcoma lesions were distributed separately, with overlap in several areas.…”
Section: Discussionmentioning
confidence: 58%
“…cHCC-CCA has been previously reported in a single patient treated with Thorotrast. 12 In that case, carcinoma lesions and angiosarcoma lesions were distributed separately, with overlap in several areas. As the present case involved a grossly well-defined single nodule containing both carcinomatous and sarcomatous lesions, we concluded that it was a multi-differentiated single tumor rather than a collision tumor.…”
Section: Discussionmentioning
confidence: 91%
“…CHCC-C was found in combination with other liver tumors, e.g., hepatic angiosarcoma in a patient with thorotrastosis (Kojiro et al 1982).…”
Section: Chcc-c Combined With Other Tumors In the Livermentioning
confidence: 93%
“…This substance was injected intravenously into humans as a radiological enhancement medium in angiography from 1927 to 1954 in Japan [2]. Following the injection, many patients have developed malignant tumors presumably due to the deposition of Thorotrast in the reticulo-endothelial system [3][4][5][6][7]. We had previously reproted that Thorotrast was deposited in human tissues mainly in the form of Th02 [8].…”
mentioning
confidence: 99%